siRNA delivery targeting to the lung via agglutination-induced accumulation and clearance of cationic tetraamino fullerene - MINAMI, Kosuke (Nature Publishing Group, 2014)
The efficient treatment of lung diseases requires lung-selective delivery of agents to the lung. However, lung-selective delivery is difficult because the accumulation of micrometer-sized carriers in the lung often induces inflammation and embolization-related toxicity. Here we demonstrate a lung-selective delivery system of small interfering RNA (siRNA) by controlling the size of carrier vehicle in blood vessels. The carrier is made of tetra(piperazino)fullerene epoxide (TPFE), a water-soluble cationic tetraamino fullerene. TPFE and siRNA form sub-micrometer-sized complexes in buffered solution and these complexes agglutinate further with plasma proteins in the bloodstream to form micrometer-sized particles. The agglutinate rapidly clogs the lung capillaries, releases the siRNA into lung cells to silence expression of target genes, and is then cleared rapidly from the lung after siRNA delivery. We applied our delivery system to an animal model of sepsis, indicating the potential of TPFE-based siRNA delivery for clinical applications.